2014
DOI: 10.1016/j.diabres.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a link between obesity, metabolic syndrome and type 2 diabetes

Abstract: :It is recognized that a chronic low-grade inflammation and an activation of the immune system are involved in the pathogenesis of obesity-related insulin resistance and type 2 diabetes. Systemic inflammatory markers are risk factors for the development of type 2 diabetes and its macrovascular complications. Adipose tissue, liver, muscle and pancreas are themselves sites of inflammation in presence of obesity. An infiltration of macrophages and other immune cells is observed in these tissues associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
1,064
4
50

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,578 publications
(1,220 citation statements)
references
References 81 publications
26
1,064
4
50
Order By: Relevance
“…Although the financial burden of high BMI raises concerns about the effectiveness of intervention strategies (3–5), increasingly more attention is placed on the role of obesity in the development of other chronic diseases (1). The relationship between obesity, cardiovascular disease (CVD), and type 2 diabetes mellitus is well documented, with high BMI associated with the development of atherosclerosis, hypertension, and insulin resistance (69). Because obesity is a clear risk factor of chronic disease, questions are raised about whether obese populations have higher rates of CVD and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the financial burden of high BMI raises concerns about the effectiveness of intervention strategies (3–5), increasingly more attention is placed on the role of obesity in the development of other chronic diseases (1). The relationship between obesity, cardiovascular disease (CVD), and type 2 diabetes mellitus is well documented, with high BMI associated with the development of atherosclerosis, hypertension, and insulin resistance (69). Because obesity is a clear risk factor of chronic disease, questions are raised about whether obese populations have higher rates of CVD and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is widely known to be complicated in pathogenesis of various diseases such as Type 2 diabetes mellitus, obesity, metabolic syndrome (Esser, Legrand‐Poels, Piette, Scheen, & Paquot, 2014; Xu et al., 2003), and cancer (Chen, Alvero, Silasi, & Mor, 2007). Several physical and chemical stimulants are factors involved in the inflammatory process such as free radicals which cause oxidative stress (Li & Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study we have shown that the ratio of IL-6, MCP-1 and IGF-1 was the lowest in the control group and increased with obesity, diabetes and diabesity. During the inflammatory process as part of chronic disease pathophysiology an increase of proinflammatory biomarkers (IL-6, IL-1β) coupled with a decrease in anti-inflammatory biomarkers (IL-10) has been demonstrated [13][14][15][16]. Other studies have shown that IL-6 and IL-1β also increased MCP-1 levels by inducing MCP-1 mRNA expression [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process in obesity includes the activation of macrophages to produce pro-inflammatory cytokines such as interleukin-1β (IL-1β) and interleukin-6 (IL-6) [13][14][15]. These proinflammatory cytokines lead to increased levels of C-reactive protein (CRP) with a demonstrable decrease in the anti-inflammatory interleukin-10 (IL-10).…”
mentioning
confidence: 99%